Skin Diseases Classification Using Hybrid AI Based Localization Approach. (29th August 2022) - Sreekala, Keshetti; Rajkumar, N.; Sugumar, R.; Sagar, K. V. Daya; Shobarani, R.; Krishnamoorthy, K. Parthiban; Saini, A. K.; Palivela, H.; Yeshitla, A.
Abstract : One of the most prevalent diseases that can be initially identified by visual inspection and further identified with the use of dermoscopic examination and other testing is skin cancer. Since eye observation provides the earliest opportunity for artificial intelligence to intercept various skin images, some skin lesion classification algorithms based on deep learning and annotated skin photos display improved outcomes. The researcher used a variety of strategies and methods to identify and stop diseases earlier. All of them yield positive results for identifying and categorizing diseases, but proper disease categorization is still lacking. Computer-aided diagnosis is one of the most crucial methods for more accurate disease detection, although it is rarely used in dermatology. For Feature Extraction, we introduced Spectral Centroid Magnitude (SCM). The given dataset is classified using an enhanced convolutional neural network; the first stage of preprocessing uses a median filter, and the final stage compares the accuracy results to the current method.